2021
DOI: 10.3390/cells10113067
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction through Oxidatively Generated Epigenetic Mark in Respiratory Viral Infections

Abstract: The bronchial vascular endothelial network plays important roles in pulmonary pathology during respiratory viral infections, including respiratory syncytial virus (RSV), influenza A(H1N1) and importantly SARS-Cov-2. All of these infections can be severe and even lethal in patients with underlying risk factors.A major obstacle in disease prevention is the lack of appropriate efficacious vaccine(s) due to continuous changes in the encoding capacity of the viral genome, exuberant responsiveness of the host immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 147 publications
0
9
0
Order By: Relevance
“…The study also found that H1N1pdm09 infection can lead to milder endothelial dysfunction. These findings suggest that COVID-19 can lead to severe vascular compromise, with the presence of microthrombi and the marked expression of inflammatory mediators [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study also found that H1N1pdm09 infection can lead to milder endothelial dysfunction. These findings suggest that COVID-19 can lead to severe vascular compromise, with the presence of microthrombi and the marked expression of inflammatory mediators [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study support the idea that both Influenza A and SARS-CoV-2 increase macrophage activation and chemokines expression. IL-6 has been established as a reliable marker for the severity and mortality of COVID-19 in clinical practice, and its antagonist has been shown to reduce mortality in hospitalized COVID-19 patients [ 5 , 7 , 9 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, commercially available pulmonary, aortic, umbilical, or cardiac primary ECs were applied. So far, the results have been controversial, emphasizing the necessity of further research to clarify the impact of SARS-CoV-2 on ECs, particularly in CVD patients, in order to account for conditions of increased oxidative stress, inflammatory cytokines, reduced vasodilation and antithrombotic features, reflecting atherosclerotic changes within the arterial wall [13,135,[158][159][160].…”
Section: Sars-cov-2 Infection Of Endothelial Cells?mentioning
confidence: 99%